Politeness Marker Change in Bima-Dompu: A Sociopragmatic Analysis of Ta from Lectures’ Perspectives - Ismail Ismail; Nur Wahyuni; Muh. Nasoha (JIBAS: Jurnal Pendidikan, Bahasa dan Sastra, 2026)
This study investigates the shift in the use of “ta” as a politeness marker in Bima and Dompu languages from a sociopragmatic perspective. In these local languages, “ta” functions as an inflectional morpheme expressing politeness, respect, and social hierarchy in communication. However, recent observations show that younger speakers increasingly replace polite forms such as iyota, madata, and buneta with less formal expressions such as iyora, even when interacting with lecturers or older people. This phenomenon reflects changing communication patterns and weakening awareness of traditional linguistic norms.This study employed a qualitative method with a sociopragmatic approach. The data were collected through semi-structured interviews with lecturers at STKIP Yapis Dompu and analyzed using thematic analysis. The findings reveal that the declining use of “ta” is influenced by digital communication, informal interaction patterns, changing perceptions of hierarchy, and reduced exposure to local cultural values among younger generations. The study concludes that the weakening use of “ta” represents not only linguistic change but also a potential erosion of cultural values embedded in Bima and Dompu languages